2020
DOI: 10.31729/jnma.5542
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Laparoscopy in Infertile Couples attending a Teaching Hospital in Eastern Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Infertility is a global health issue and a socially destabilizing condition for couples with several stigmas including medical, social, psychological burdens and a marital disharmony. The aim was to study the outcome of laparoscopy in infertile females attending Nobel Medical College as laparoscopy is considered as a gold standard in investigation and treatment of infertility. Methods: A descriptive cross-sectional study was carried out in the department of Obstetrics and Gynaecology over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Also similar to the study of Pantou et al [27] who showed (23.3%) were diagnosed with periadnexal and pelvic adhesions.…”
Section: Detectedsupporting
confidence: 90%
“…Also similar to the study of Pantou et al [27] who showed (23.3%) were diagnosed with periadnexal and pelvic adhesions.…”
Section: Detectedsupporting
confidence: 90%
“…9 But such pathology was seen in 50% of cases in different forms. 24 Arojoki et al observed that the prevalence of abnormal thyroid stimulating hormone (TSH) among the subfertile couples was highest in the ovulatory dysfunction (6.3%) and unexplained subfertility (4.8%) groups and lowest in the tubal subfertility (2.6%) and male subfertility (1.5%) groups. 25 7,14,11 Only male factor contributed in approximately 16 (11.4%) cases of this study.…”
Section: Multiple Aetiological Factors Have Been Identifiedmentioning
confidence: 99%